Versöhnung durch Wahrheit? Eine vergleichende Betrachtung der südafrikanischen Wahrheits- und Versöhnungskommission und der Enquete-Kommission zur Aufarbeitung von Geschichte und Folgen der SED-Diktatur in Deutschland - Burkard, Hannah Katharina (Recht und Verfassung in Afrika - Law and Constitution in Africa, 2022)
In the context of comparative legal history, the South African Truth and Reconciliation Commission is contrasted with the Study Commission for Working Through the History and the Consequences of the SED Dictatorship in Germany. In an extensive examination, central aspects of the commissions' mandates and their implementation are analyzed, thus providing a deeper understanding of the two truth commissions. Whilst the final reports of the commissions serve as a central source, personal interviews with experts in transitional justice and contemporary witnesses from South Africa are also included in the work.